Systemic Therapy Type and Timing Effects on Radiation Necrosis Risk in HER2+ Breast Cancer Brain Metastases Patients Treated With Stereotactic Radiosurgery - Park, Christine; Buckley, Evan D.; Van Swearingen, Amanda E. D.; Giles, Will; Herndon, James E.; Kirkpatrick, John P.; Anders, Carey K.; Floyd, Scott R. (Frontiers in Oncology, 2022)
Background There is a concern that HER2-directed systemic therapies, when administered concurrently with stereotactic radiosurgery (SRS), may increase the risk of radiation necrosis (RN). This study explores the impact of timing and type of systemic therapies on the development of RN in patients treated with SRS for HER2+ breast cancer brain metastasis (BCBrM). Methods This was a single-institution, retrospective study including patients ≥18 years of age with HER2+ BCBrM who received SRS between 2013-2018 and with at least 12-month post-SRS follow-up. Presence of RN was determined via imaging at one-year post-SRS, with confirmation by biopsy in some patients. Demographics, radiotherapy parameters, and timing (“during” defined as four weeks pre- to four weeks post-SRS) and type of systemic therapy (e.g., chemotherapy, HER2-directed) were evaluated. Results Among 46 patients with HER2+ BCBrM who received SRS, 28 (60.9%) developed RN and 18 (39.1%) did not based on imaging criteria. Of the 11 patients who underwent biopsy, 10/10 (100%) who were diagnosed with RN on imaging were confirmed to be RN positive on biopsy and 1/1 (100%) who was not diagnosed with RN was confirmed to be RN negative on biopsy. Age (mean 53.3 vs 50.4 years, respectively), radiotherapy parameters (including total dose, fractionation, CTV and size target volume, all p>0.05), and receipt of any type of systemic therapy during SRS (60.7% vs 55.6%, p=0.97) did not differ between patients who did or did not develop RN. However, there was a trend for patients who developed RN to have received more than one agent of HER2-directed therapy independent of SRS timing compared to those who did not develop RN (75.0% vs 44.4%, p=0.08). Moreover, a significantly higher proportion of those who developed RN received more than one agent of HER2-directed therapy during SRS treatment compared to those who did not develop RN (35.7% vs 5.6%, p=0.047). Conclusions Patients with HER2 BCBrM who receive multiple HER2-directed therapies during SRS for BCBrM may be at higher risk of RN. Collectively, these data suggest that, in the four-week window around SRS administration, if HER2-directed therapy is medically necessary, it is preferable that patients receive a single agent.